Stiffening effects-controlling sizing procedure of ADAS dampers in seismic retrofit of frame structures - Terenzi, Gloria; Sorace, Stefano; Fuso, Elena (Frontiers in Built Environment, 2023)
Added Damping and Stiffness (ADAS) steel dissipators are among the most classical devices installed in dissipative bracing systems for the advanced seismic retrofit of frame buildings. An energy-based sizing procedure is formulated in this study for this class of dampers, where the total number of constituting plates is directly related, without iterative steps, to the supplementary damping energy required to jointly reduce stress states in structural members and storey drifts. The stiffening effects of the dissipative braces are expressly controlled, so as to compensate for the increase in storey shears induced by their incorporation in the frame skeleton. The sizing procedure is demonstratively applied to the retrofit design of a 6-storey reinforced concrete building, to explicate and discuss the use of its analytical relations and relevant limitations in practice. The evaluation of the seismic performance of the structure in retrofitted conditions allows comparing the response of the dissipative bracing system with the hypotheses formulated at the sizing stage.